AN ANALYSIS OF LANGUAGE IN “THE GREAT GATSBY” MOVIE - ANGELIA JOVANKA RANTUNG; Sanerita Tresnawati Olii; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
Analyzed the language style that use in “The Great Gatsby” movie was the purpose in this research. The theory of Martin Joos (1967) with the five differentiate styles namely frozen style, formal style, casual style, consultative style and intimate style were used to analyzed the language style in this research. In Conducting this research, descriptive qualitative method were used. The data were collected through watching the movie and reading the script of the movie. The steps of Miles and Huberman (1994:10) were used to analyzed the data, they were data reduction, data display and drawing conclusion. The result showed that there were one hundred and sixty-three (163) data included in five kinds of language style. There were zero (0) data in frozen style, thirty (30) data in formal style, one hundred and eight (108) data in casual style, fifteen (15) data in consultative style and ten (10) data in intimate style. Casual style was dominantly in “The Great Gatsby” movie which found one hundred and eight (108) data. This study was focusing on the language style that used in a movie that usually we watch in the cinema or in the television. Through this research, the researcher hopes people can improve their speaking habits, know the language etiquette and use the right language style in the right place and for the right person. There are some suggestions for the future researcher who interested to analyze language style, they can conduct the study about the language style that taken from another media such as in the novel, comic book, or short movie from the youtube creator because nowadays, there are a lot of youtube content creator who made interesting short movie and the future researcher might use another theory of language style from the experts to give more knowledge about the language style in the other media.